Videomodelação e videomodelação com feedback em treino parental remoto para o desenvolvimento de habilidades de mando em crianças TEA - Tufolo, Alice Passos (2025)
The prevalence of children with ASD has been growing exponentially in recent years. Along with this increase comes the lack of access to intervention, either because it is costly, because families live in hard-to-reach areas, or because of a shortage of trained professionals to serve the number of children. One of the solutions to this issue indicated in the literature has been parent training; however, this strategy still requires the presence of professionals for instruction, as well as often having a high financial cost. Digital technology thus appears as a possible way to solve difficulties faced by caregivers, such as living in hard-to-reach regions and the need for the presence of a professional. The present work carried out two studies aimed at developing parent training strategies. Study 1 sought to update the production on parent training through a scoping review of research in behavior analysis, focusing on early interventions for children with ASD aged 0 to 5 years, considering better prognoses in early interventions, in order to evaluate a parent training proposal that attempts to minimize the demands for the presence of a professional, remotely, that may have a lower intervention cost. Study 2 aimed to a) evaluate which of the procedures, video modeling or video modeling + feedback, shows better results in terms of effectiveness when training caregivers' skills to remotely teach communication skills to their children diagnosed with ASD, through manding; and b) evaluate the maintenance, generalization, and social validity of the skills taught. Five dyads, caregiver and child, participated, receiving remote intervention in their homes. The results of Study 1 showed that: a) there are various caregiver teaching strategies regardless of the behavior being worked on, with a predominance of instructions and classes, followed by feedback and modeling (in person or by video); b) the most frequently taught behaviors involve managing challenging behavior and communication; c) few studies evaluated generalization and social validity; d) family characteristics such as support networks were also not considered, nor were these characteristics compared with their performance. The results of Study 2, evidenced by the use of the adapted alternating treatments experimental design, indicate that video modeling with feedback was the most effective procedure for teaching various mands, that the acquisition of teaching behaviors by parents generally resulted in the acquisition of mands taught by children, and that the behaviors generalized to other environments